PENGARUH MODEL PEMBIAYAAN, RISIKO PEMBIAYAAN, RASIO KAPITALISASI, DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA (PERIODE 2018 – 2022) - Zahra, Erneta Aisyia; Mutmainah, Siti (Diponegoro Journal of Accounting, 2024)
This research aims to analyze the influence of financing models and bank management behavior on the profitability of islamic commercial banks in Indonesia. The research considers profit-sharing financing, profit margin financing, financing risk, capitalization ratio, and operational efficiency as independent variables. The dependent variable in this research is profitability, proxied by Return on Assets (ROA).The population used in this research consists of islamic commercial banks registered with the OJK during the period of 2018-2022. The sample selection in this research used census sampling, resulting in 10 islamic commercial banks within the specified period. There are 47 final samples in this research. The analysis method used is panel data regression analysis with the help of E-views 13 application in testing the hypotheses.The results of this research show that the profit margin financing has a significant positive relationship with profitability. Meanwhile, operational efficiency has a significant negative relationship with profitability. This research also found that profit-sharing financing, financing risk, and capitalization ratio do not have an influence on profitability.